Leveraging scientific modeling to engage pre-med undergraduates in physics lab courses - Madeline Harmer; Adam Bennion; Alexandra M. Hopps-McDaniel; Jeannette Lawler; Nathan Powers (Physical Review Physics Education Research)
Undergraduate students on track for medical school are often required to take general physics lab courses. Many of these students carry an attitude of obligation into these courses which can make it challenging for instructors to engage students in course material. We address the question: How does engaging with medically based models in introductory physics labs affect pre-med undergraduate perceptions of the modeling process and their perceptions of science? We redesigned an electricity and magnetism lab in an introductory physics lab course, where approximately 70% of the undergraduates reported plans to attend medical school. We situated the lab in the mechanics of MRI magnetic resonance and collected data on the participants’ experiences through surveys and lab submissions. As a part of the analysis, we modified a rubric to evaluate engagement in modeling and applied grounded coding theory to the survey responses to develop themes of the participants’ understanding of scientific modeling. The participants’ understanding and engagement in scientific modeling increased during the newly developed lab and remained high for subsequent labs. We recommend that instructors of undergraduate nonmajor labs consider the demographic of their student population and design lab experiences situated within their interests and focus on central science practices like modeling.